Hypnobirthing Counseling for Pregnant Women at Mahdalena Pane Clinic in 2019 - Arva Rochmawati; Dwi Ris Hasanah (Science Midwifery, 2020)
The purpose of this research is to provide useful information and input for the community or pregnant women about the benefits of hypnobirthing for pregnancy, not only during pregnancy, but also before delivery, during labor and after delivery. That hypnobirthing helps cope with pain without the involvement of drugs. Increase knowledge of pregnant women about hypnobirthing for pregnancy, increase knowledge of pregnant women about the benefits of hypnobirthing during childbirth, after delivery and during the postpartum period. The types and forms of activities of this activity are providing counseling materials to pregnant women about hypnobirthing, telling mothers the difference between childbirth and hypnobirthing, with regular delivery or caesarean section. To achieve the objectives of the above activities, activities were carried out including providing counseling materials about the benefits of hypnobirthing for pregnancy, not only during pregnancy, but also before delivery, during labor and after delivery. That hypnobirthing helps cope with pain without the involvement of drugs.